Gopal Krishna Gokhale: Gandhi's political guru - Talwalkar, Govind (New Delhi Pentagon, 2015)
Mahatma Gandhi said, Gopal Krishna Gokhale was his political Guru and a true servant of India. Gokhale's motto was to spiritualize the public life. His noble dream was the Servants of India Society , which he founded. Gokhale was a professor and then principal of the Ferguson College, Pune. He was a great liberal, parliamentarian and president of the Indian National Congress. His mentor, Justice M.G. Ranade started the Sarvajanik Sabha Journal. Gokhale Assisted him. Gokhale's deposition before the Welby Commission on the financial condition of India won him accolades. His speeches on the budget in the Central Legislative Council were unique, with thorough statistical analysis. He appealed to the reason. He played a leading role in bringing about Morley-Minto Reforms, the beginning of constitutional reforms. It is noteworthy that this book is being published in the centenary year of Gandhi's return to India from South Africa. Gokhale's death centenary was on 19 February 2015, while his 150th birth anniversary is next year.
Keywords: Political Science; Political ideology; Nationalism